Effect of different grazing periods in elephant grass pasture upon milk production - Cóser, Antônio Carlos; Martins, Carlos Eugênio; da Fonseca, Dilermando Miranda; Salgado, Luís Tarcísio; Alvim, Maurilio José; Teixeira, Flavio Valeriano (Pesquisa Agropecuaria Brasileira, 1999)
Elephant grass (Pennisetum purpureum Schum. cv. Napier) pastures were grazed by lactating dairy cows with the aim of assessing the best grazing period to maximize milk production. Three grazing periods (1, 3 and 5 days, with 30 days resting) were tested using a randomized block design, with two replications, during three years. Each paddock was grazed by 4 milking cows. During the experimental period, the cows received individually 2,0 kg/day of a concentrate mixture. Estimates of forage availability and quality, plant height, ground cover and milk production, were recorded. Results showed that available forage and quality and milk production were not influenced by the three different grazing periods. Average milk production/cow/day in the rainy season were 10.9, 10.8 and 10.8 kg and the average milk yields per hectare were 7,848, 7,800 and 7,776 kg/ha for 1, 3 or 5 grazing days, respectively (P>0.05). The largest flotations in dairy milk yield per cow occurred in the five grazing days treatment, explained for both forage availability and quality decreases along the grazing period on each paddock.